Implementasi Model Problem Solving dalam Meningkatkan Keterampilan Berpikir Kritis Siswa SMP Negeri 8 Tanah Putih - Dewi, Ratna; Nasution, Mustafa; Siregar , Desi Ana Sari (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the Problem-Solving model in improving students’ critical thinking skills at SMP Negeri 8 Tanah Putih. The research method used is Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which involves planning, action, observation, and reflection in two cycles. The research subjects were eighth-grade students, with data collected through observation, tests, and interviews. The results indicate that the implementation of the Problem-Solving model significantly enhances students’ critical thinking skills, as reflected in the improvement of average scores across cycles. Additionally, this model encourages students to be more active in analyzing, evaluating, and solving problems both independently and in groups. Thus, the Problem-Solving model can be an effective instructional strategy to enhance critical thinking skills and student autonomy at the junior high school level.